Effect of the total flavonoids of Dracocephalum moldavica L. on metabolic associated fatty liver disease in rats - Sun, Xiaoyu; Ge, Na; Liang, Qingqing; Wang, Qian; Yu, Hui; Jin, Min (Frontiers in Pharmacology, 2025)
IntroductionMetabolic-associated fatty liver disease (MAFLD) is a liver disease syndrome. The total flavonoids of Dracocephalum moldavica L. (D. moldavica), the main active components of D. moldavica, have been demonstrated not only to have anti-inflammatory and antioxidant effects but also to regulate gut microbiota. However, the mechanism by which it improves MAFLD is unclear. So we want to investigate how the total flavonoids of D. moldavica alleviate high-fat diet (HFD)-induced MAFLD in rats.MethodsFirstly, MAFLD rat models were established by feeding with HFD, while the total flavonoids of D. moldavica were administered via gavage. Then, the experiments analyzed the changes of gut microbiota by the 16S rRNA sequencing and detected intestinal barrier permeability and liver inflammation to explore the mechanism of the total flavonoids of D. moldavica in the prevention and treatment of MAFLD.ResultsWe found that the total flavonoids of D. moldavica reduced systemic inflammation and could alleviate serum and liver lipid metabolism disorders in MAFLD rats. The results of the 16S rRNA sequencing demonstrated that the total flavonoids of D. moldavica increased the abundance and diversity of gut microbiota. Furthermore, the total flavonoids of D. moldavica have been demonstrated to enhance the intestinal mucosal barrier function, reduce LPS translocation, and inhibit the activation of hepatic TLR4/MyD88/NF-κB pathway. This could effectively ameliorate the hepatic lesions in MAFLD rats.ConclusionsThe aforementioned outcomes indicate that the total flavonoids ofD moldavica may potentially alleviate MAFLD by modulating gut microbiota, intestinal mucosal barrier and hepatic inflammation.